Effect of water deficit on maize seeds (Zea mays L.) during germination - Kolesnikov, Maksym; Herasko, Tetiana; Paschenko, Yuliia; Pokoptseva, Liubov; Onyschenko, O.; Kolesnikova, A.; Колесніков, Максим Олександрович; Герасько, Тетяна Володимирівна; Пащенко, Юлія Петрівна; Покопцева, Любов Анатоліївна (Tartu, Estonia : Institute of Technology, EMU, 2023)
EN: Global climate changes cause the frequent recurrence of droughts, which reduce crop production more than any other environmental factor. This study was conducted to access the effect of water deficit on maize seeds (Zea mays L.) DKC 5143 hybrid during germination. The tasks were to assess the influence of different rank of osmotic stress on the maize lipid peroxidation (LPO), proline content, catalase and aminotransferases activities, and morphometric parameters during the early stages of maize seeds germination. The maize seeds were exposed to five levels of water availability which produced by PEG-1500 solutions (0, 20, 50, 100, 200 g L-1). Seeds of maize were germinated on Petri dishes for 7 days under controlled parameters. Amounts of TBARS were increased in maize sprouted seeds by 1.9 times, coleoptiles by 1.4 times, and in roots - by 1.9 times under water deficit. Proline content increased by 9.2 times in coleoptiles and by 6.0 times in 7 days maize roots while PEG-1500 (200 g L–1) treatment. An increasing of catalase (CAT), aminotransferases (ALT, AST) activities according to osmotic potential value was also observed. A remarkable development of maize oxidative reaction was associated with a significant reduction in emergence, wet weight and length of water-stressed plants. These results assume that the maize adaptive strategy to osmotic stress during germination was found in the activation of LPO and antioxidant components. The findings provide useful help for correcting the stress state of maize using osmotically active regulators.
Keywords: aminotransferases; catalase; drought; germination; lipid peroxidation; maize; osmotic stress; proline